Sago biomass as a sustainable source for biohydrogen production by Clostridium butyricum A1 - Jenol, Mohd Azwan; Ibrahim, Mohamad Faizal; Phang, Lai Yee; Md Salleh, Madihah; Abd. Aziz, Suraini (North Carolina State University * College of Natural Resources, 2014)
Biohydrogen production from biomass is attracting many researchers in developing a renewable, clean and environmental friendly biofuel. The biohydrogen producer, Clostridium butyricum A1, was successfully isolated from landfill soil. This strain produced a biohydrogen yield of 1.90 mol H2/mol glucose with productivity of 170 mL/L/h using pure glucose as substrate. The highest cumulative biohydrogen collected after 24 h of fermentation was 2468 mL/L-medium. Biohydrogen fermentation using sago hampas hydrolysate produced higher biohydrogen yield (2.65 mol H2/mol glucose) than sago pith residue (SPR) hydrolysate that produced 2.23 mol H2/mol glucose. A higher biohydrogen productivity of 1757 mL/L/h was obtained when using sago hampas hydrolysate compared to when using pure glucose that has the productivity of 170 mL/L/h. A comparable biohydrogen production was also obtained by C. butyricum A1 when compared to C. butyricum EB6 that produced a biohydrogen yield of 2.50 mol H2/mol glucose using sago hampas hydrolysate as substrate. This study shows that the new isolate C. butyricum A1 together with the use of sago biomass as substrate is a promising technology for future biohydrogen production.